Non-communicable Diseases, Big Data and Artificial Intelligence - Wang, Youxin; Feng, Ming (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This reprint includes 15 articles in the field of non-communicable Diseases, big data, and artificial intelligence, overviewing the most recent advances in the field of AI and their application potential in 3P medicine.